Evaluation of flavor & aroma compounds during fermentation of coconut (Cocos nucifera Linn.) sap. - Tenedero, Lourdes Rae Louise
The sap of the coconut can be fermented to make the product known as tuba. The production of this product is one of the sources of livelihood and very common in the Philippines. Evaluation of flavor and aroma compounds during fermentation of tuba collected from Brgy. Baras, Guimbal, Iloilo was done. Physicochemical analysis, specifically pH, total soluble solids (TSS), % TA and % alcohol was also performed. Analysis (3 runs) was done at three fermentation periods, namely, 0-3 hours, 8-11 hours and 21-24 hours after sample collection. Quantitative descriptive analysis (QDA) was done to evaluate the flavor and aroma compounds while headspace-solid phase microextraction gas chromatography mass spectrometry (HS-SPME-GC-MS) was done to idebtify the volatile composition of tuba. Tuba leans more towards the sweet taste but becomes more bitter, slightly astringent and sour as fermentation time increases. For all three fermentation periods, the dominant aroma detected was fruity. Through HS-SPME GC-MS, a total of 12 compounds were identified belonging to three chemical groups, namely, esters, acids and alcohols. Volatile compounds belonging to esters were ethyl hexanoate, ethyl octanoate, ethyl-9-decenoate, ethyl decanoate, 3-methyl-1-butanol acetate and ethyl acetate which could be associated with fruity aroma. Acids identified were acetic acid, formamide, propanoic acid and octanoic acid, which contribute to the sourness in flavor as well as unpleasant or pungent odor of tuba. Alcohols, namely ethyl alcohol, 3-methyl-1-butanol and phenylethyl alcohol were identified and are associated with alcoholic aroma as well as bitter, astringent and alcoholic flavor. The pH of tuba which rangd from 3.72 to 3.5 did not significantly decreased. There is a significance in the decrease of TSS of tuba from 11.1 to 5.51 0Brix. in %TA, the increase from 0.468% to 0.620 was not significant. Also, the alcohol content of tuba which ranged from 5.00 to 6.12% did not significantly increased. The volatiles identified are due to the by-product of the reactions during fermentation which affects the flavor and aroma of tuba. In general, it can be concluded that the volatile compunds identified through HS-SPME GC-MS contributed to the flavor and aroma of tuba as evaluated through sensory evaluation. The findings could therefore be used to evaluate tuba and identify sensory attributes that can be used as quality indicator.